2016
DOI: 10.3892/ijmm.2016.2626
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin inhibits UVA-induced cytotoxicity in vitro and prevents signs of skin aging in vivo

Abstract: Apigenin (4',5,7-trihydroxyflavone) is a flavone that has been reported to have anti-inflammatory, antioxidant and anti-carcinogenic properties. In this study, we investigated the protective effects of apigenin on skin and found that, in experiments using cells, apigenin restored the viability of normal human dermal fibroblasts (nHDFs), which had been decreased by exposure to ultraviolet (UV) radiation in the UVA range. Using a senescence-associated (SA)-β-gal assay, we also demonstrate that apigenin protects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 40 publications
0
42
0
1
Order By: Relevance
“…Results showed that pain, nausea, vomiting, photophobia, and phonophobia significantly decreased [201]. Topic application of apigenin-containing cream in 20 women reduces skin aging, besides increasing dermal density and elasticity [245]. In addition, treatment with a flavonoid mixture composed of 20 mg epigallocathechin-gallate plus 20 mg apigenin for 2-5 years reduced the recurrence rate of colon neoplasia in patients with resected colon cancer [246].…”
Section: Apigeninmentioning
confidence: 98%
“…Results showed that pain, nausea, vomiting, photophobia, and phonophobia significantly decreased [201]. Topic application of apigenin-containing cream in 20 women reduces skin aging, besides increasing dermal density and elasticity [245]. In addition, treatment with a flavonoid mixture composed of 20 mg epigallocathechin-gallate plus 20 mg apigenin for 2-5 years reduced the recurrence rate of colon neoplasia in patients with resected colon cancer [246].…”
Section: Apigeninmentioning
confidence: 98%
“…Furthermore, a clinically meaningful but nonsignificant trend was noted for a greater reduction in total HAM-D scores for chamomile versus placebo in participants with current comorbid depression provided evidence that chamomile may provide clinically meaningful antidepressant activity. Choi et al [225] demonstrated the clinical efficacy of apigenin on aged skin, using an apigenin-containing cream on forty women, aged over 30 years, through a randomized and double-blinded clinical trial with four weeks of treatment. Application of apigenin-containing cream increased dermal density and elasticity, and reduced fine wrinkle length along with improved skin evenness, moisture content and transepidermal water loss, compared to the placebo group.…”
Section: 0 Clinical Trials With Apigeninmentioning
confidence: 99%
“…Among the various types of light affecting the skin, ultraviolet A (UVA) is the primary contributor to skin photoaging because it is not absorbed by any laminar flow and potently penetrates the skin ( 1 , 2 ). Previous studies have demonstrated that the probability of skin aging is doubled in populations with high UV exposure compared with populations with lower exposure, and skin aging occurs ≤10 years earlier in such populations ( 3 5 ).…”
Section: Introductionmentioning
confidence: 99%